New Insights to Investigate the Impact of Internal Control Mechanisms on Firm Performance: A Study in Oman - Alabdullah, Tariq Tawfeeq Yousif; Ahmed, Essia Ries (Riset Akuntansi dan Keuangan Indonesia, 2021)
Based on what has been done in accounting, economic and finance literature, the key aim of the this research is to analyze the link among the ownership’s characteristics variables and market share (M-Share) to represent firm financial performance in financial firms listed in Oman in its Stock Exchange market. The present research conducts regression model to show the effect of control mechanisms on market share (M-Share) that represented by firm performance with determining other control variables. We used panel data of Muscat Stock Exchange financial firms over the period 2011-2019. We found that foreign ownership (F-Own) and management ownership variables affected by positively by market share (M-Share), where market share (M-Share) reflects firm financial performance as dependent variable in the current research. Also we utilized firm size as a control variables and the findings show that there is a positive impact on performance where the industry has a negative impact on performance. The implication of this research from practical perspective suggests that good control mechanisms is also important for all kind of firms and this also must enhance the interest of stakeholders to the firm. The Originality and value of the present research from the perspective of GCC countries is to examine the link between ownership characteristics and market share (M-Share) as indicator of firm performance. So, the current research adds to the literature and studies in emerging markets of GCC by investigating the link with such an insight so that it enhances the strengths of the existing literature review that deals with such a link. The findings of the present research link will be approximately useful to the authorities, regulatory bodies, policymakers and also for stakeholder.